2006
DOI: 10.1063/1.2336211
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-grained V representability

Abstract: The unsolved problem of determining which densities are ground state densities of an interacting electron system in some external potential is important to the foundations of density functional theory. A coarse-grained version of this ensemble V-representability problem is shown to be thoroughly tractable. Averaging the density of an interacting electron system over the cells of a regular partition of space produces a coarse-grained density. It is proved that every strictly positive coarsegrained density is co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 18 publications
(27 reference statements)
1
26
0
Order By: Relevance
“…The problem of N-representability has been solved, and it can be shown that any non-negative function can be written in terms of some antisymmetric Ψ(r 1 , · · · , r N ) in the form (2.2) [56,60]. The v-representability problem is still an ongoing investigation, although some results regarding it can be found in [37,155,92].…”
Section: Density Functional Theory (Dft) Formalismmentioning
confidence: 99%
“…The problem of N-representability has been solved, and it can be shown that any non-negative function can be written in terms of some antisymmetric Ψ(r 1 , · · · , r N ) in the form (2.2) [56,60]. The v-representability problem is still an ongoing investigation, although some results regarding it can be found in [37,155,92].…”
Section: Density Functional Theory (Dft) Formalismmentioning
confidence: 99%
“…13 Since the lattice can be arbitrarily dense, this effectively solves the V-representability problem in DFT. In a related approach, V-representability was recently proven by Lammert 14 for coarse-grained systems.…”
Section: Dft On Lattice Spacesmentioning
confidence: 99%
“…Building on the results of §4, the existence and regularity results for the coarse-grained theory will be presented in §6. In addition to the considerably simpler and more intuitive proofs, those results go beyond the previous version of the theory [20][21][22] by treating spin-densities.…”
Section: Coarse-grainingmentioning
confidence: 99%
“…This section reviews the basic notions of the coarsegrained DFT framework [20][21][22] , augmented to handle SDFT. Much of it looks nearly the same on the surface as the conventional fine-grained theory of §2.…”
Section: Coarse-grainingmentioning
confidence: 99%
See 1 more Smart Citation